2004
DOI: 10.1007/s10266-004-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

Heat curing of UTMA-based hybrid resin: effects on the degree of conversion and cytotoxicity

Abstract: This study was designed to determine the effects of the heat curing time on a urethane tetramethacrylate (UTMA)-based hybrid resin and specifically on the degree of conversion (DC) and cytotoxicity. The materials used in this study were Estenia, a new-generation hybrid resin, and an experimental fiber reinforcement, Br-100. The DC values of the hybrid resin samples were measured using a Fourier transform infrared (FTIR) spectrophotometer after 180 s of light curing followed by heat curing (0, 15, 30, and 60 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Leveraging the advances in adhesive bonding technology, the conservative approach of minimally invasive dentistry allows the esthetics and function of anterior teeth to be restored with adhesive fixed partial dentures. Fueled by increasing interest in metal-free esthetic dentistry, glass fiber-reinforced composite (FRC) has been used in myriad dental applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Of particular interest to this paper are the adhesive fixed partial dentures (AFPDs), which have been favorably reported because of their good clinical performance [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the advances in adhesive bonding technology, the conservative approach of minimally invasive dentistry allows the esthetics and function of anterior teeth to be restored with adhesive fixed partial dentures. Fueled by increasing interest in metal-free esthetic dentistry, glass fiber-reinforced composite (FRC) has been used in myriad dental applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Of particular interest to this paper are the adhesive fixed partial dentures (AFPDs), which have been favorably reported because of their good clinical performance [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Säilynoja et al 22) suggested that temperature changes reduce flexural strength due to internal stress generated within the material. Both materials used in this study were composite materials containing matrix resin, glass-based filler, and glass fibers, which have different coefficients of thermal expansion.…”
Section: Effects Of Temperature Changementioning
confidence: 99%
“…The bonding property at the reinforcement/matrix interface is a critical factor affecting the mechanical properties of composite materials. In particular, the addition of filler particles to a bonding agent and substantially active silane-coupling treatment enhance interfacial bonding between the fibers and the hybrid resin matrix, improving the flexural strength of FRC [21][22][23][24] . In clinical practice, patients receiving prosthetics made of such materials have numerous concerns, including safety, durability, breakage, the effect of brushing on the shiny appearance, and whether to expect marginal leakage.…”
Section: Introductionmentioning
confidence: 99%
“…As with any prosthetic devices, the materials used for fabricating FPDs play a pivotal role in determining the success rate and longevity of these dental restorations. In the case of FRC FPDs, numerous studies were carried out to examine the FRC material from different perspectives: mechanical properties [7][8][9][10] , material development in terms of flexural strength 11) , biocompatibility 12) , fatigue analysis 13,14) , structural analysis in terms of stress distribution 15,16) , and optimal design of FRC framework to obtain the maximum reinforcement effect for FPD 17,18) . Despite the much that is already known about the material properties of FRC framework and particulate-filled composite veneer through the numerous laboratory and clinical studies, much remains to be known about the mechanical behavior of FRC FPDs with respect to displacement and stress magnitude and distribution pattern which were induced during functional loading.…”
Section: Introductionmentioning
confidence: 99%